Collateral imposition and financial inclusion: A case study among Islamic banks and MSMEs in Indonesia - Adi Saifurrahman; Salina Kassim (Islamic Economic Studies (IES), 2022)
Purpose The primary objective of this paper is to identify and compare the collateral imposition practices among Islamic banks in Indonesia to serve micro, small and medium-sized enterprise (MSME) clients and explore the experiences and perceptions of MSME entrepreneurs pertaining to collateralisation in MSME financing. Design/methodology/approach This study was carried out by implementing a case study research strategy. The data was gathered primarily through the interview by utilising purposive uncontrolled quota sampling. The interview was conducted using semi-structured interview questions by targeting the two sides of Islamic financial inclusion: the Islamic banking industry (supply-side) and the MSME segment (demand-side). Findings This paper implies that the collateral provision is indeed an obligatory requirement for MSME to access regular financing in an Islamic bank, preferably the immovable type that consists of land and property. Subsequently, although the Islamic banks offer non-collateralised financing, their disbursement is still relatively scant and limited. Furthermore, despite the collateral issues, most MSME entrepreneurs positively perceive the bank's collateralisation practice, indicating their awareness and understanding of the collateral purpose and function to access the financing facility. Research limitations/implications This paper merely observed six Islamic bank institutions and 22 MSME units in urban and rural areas in Indonesia using a case study approach. Therefore, the empirical findings and case discussions were limited to those around the corresponding Islamic banks and MSME participants. Practical implications By referring to the several disclosed issues associated with the collateral imposition practices, this paper presents several recommendations that might be considered by the policymakers and the Islamic banking industry to enhance the realisation of MSME Islamic financial inclusion from the collateral implementation aspect, and thereby, facilitating more inclusive growth for the MSME industry. Originality/value This paper is unique since the paper attempts to analyse and compare the collateral imposition practices and its perception from the two distinct sides of Islamic financial inclusion that were represented by Islamic banks and MSMEs in Indonesia by including different types of Islamic banks and different segments of MSME in their diverse business sector within the urban and rural locations.
Keywords: D10; G21; G40; O17; 330; Collateral; Financial inclusion; Indonesia; Islamic banks; MSME